The role of the potassium channel gene KCNK2 in major depressive disorder. Issue 3 (28th February 2015) - Congiu, Chiara; Minelli, Alessandra; Bonvicini, Cristian; Bortolomasi, Marco; Sartori, Riccardo; Maj, Carlo; Scassellati, Catia; Maina, Giuseppe; Trabucchi, Luigi; Segala, Matilde; Gennarelli, Massimo
Abstract: Six single nucleotide polymorphisms (SNPs) of the KCNK2 gene were investigated for their association with major depressive disorder (MDD) and treatment efficacy in 590 MDD patients and 441 controls. The A homozygotes of rs10779646 were significantly more frequent in patients than controls whereas G allele of rs7549184 was associated with the presence of psychotic symptoms and the severity of disease. Evaluating the Sequenced Treatment Alternatives to Relieve Depression (STAR⁎D) dataset, we confirmed our findings. Highlights: We analyzed KCNK2 variants in 590 MDD of whom 372 TRD and 441 controls. The association with one SNP confirmed the role of KCNK2 in MDD susceptibility. Another SNP was associated with severity and presence of psychotic symptoms. We confirmed data on severity in a replication sample (STAR⁎D). Our results indirectly explain the role of KCNK2 in treatment efficacy.